2014
DOI: 10.3233/jad-132033
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia and Bleomycin Hydrolase Modulate the Expression of Mouse Brain Proteins Involved in Neurodegeneration

Abstract: Homocysteine (Hcy) is a risk factor for Alzheimer's disease (AD). Bleomycin hydrolase (BLMH) participates in Hcy metabolism and is also linked to AD. The inactivation of the Blmh gene in mice causes accumulation of Hcy-thiolactone in the brain and increases susceptibility to Hcy-thiolactone-induced seizures. To gain insight into brain-related Blmh function, we used two-dimensional IEF/SDS-PAGE gel electrophoresis and MALDI-TOF/TOF mass spectrometry to examine brain proteomes of Blmh-/- mice and their Blmh+/+ l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 61 publications
0
34
0
Order By: Relevance
“…These findings suggest that while in the kidney and liver the antioxidant defense is enhanced by a high-Met diet, in the brain the antioxidant defense is compromised. The other proteins that were identified as differentially expressed in the kidney (Table 1) were not regulated by the Pon1 −/− genotype and/or high-Met diet in the liver [24] or brain [25]. Pebp1 was up-regulated in the kidney and down-regulated in the brain both by the Pon1 −/− genotype and highMet diet (Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These findings suggest that while in the kidney and liver the antioxidant defense is enhanced by a high-Met diet, in the brain the antioxidant defense is compromised. The other proteins that were identified as differentially expressed in the kidney (Table 1) were not regulated by the Pon1 −/− genotype and/or high-Met diet in the liver [24] or brain [25]. Pebp1 was up-regulated in the kidney and down-regulated in the brain both by the Pon1 −/− genotype and highMet diet (Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 94%
“…Protein sample preparation, 2D-IEF/SDS-PAGE analyses, and protein identification by MALDI-TOF mass spectrometry [23][24][25] were carried out as described in the Supplementary Methods.…”
Section: Proteomic Analysesmentioning
confidence: 99%
“…In humans and mice, HHcy leads to the accumulation of Hcy-thiolactone and N -Hcy-protein, in addition to Hcy (Chwatko et al 2007 ; Jakubowski et al 2008 , 2009 ). We and other investigators have shown that HHcy induces changes in gene expression in mouse models that are associated with atherothrombotic disease (Devlin et al 2005 ; DiBello et al 2010 ; Ingrosso et al 2003 ; Kim et al 2011 ; Pogribny et al 2008 ; Sharma et al 2006 ; Suszynska-Zajczyk et al 2014a , b , c , d ). However, it is not known what mechanism(s) are involved and which metabolite—Hcy itself, Hcy-thiolactone, or N -Hcy-protein—is responsible for changes in gene expression.…”
Section: Introductionmentioning
confidence: 89%
“…However, some (eg. ATP5D, ATP5E, NDUFA4, NDUFB5, NDUFB6) have been implicated in other neurodegenerative disorders (Chen et al, 2014 ; Suszyńska-Zajczyk et al, 2014 ). Additionally, NDUFC2, ND2, COX7C, NDUFV3, SDHC, ATP5C1, COX6A1, ATP4B, ATP6V1D , and COX17 are associated with mitochondrial function or impaired bioenergetic metabolism, and thus further support a role for mitochondrial dysfunction in the cell autonomous degeneration of motor neurons in sporadic ALS (Burman et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%